Penyalahgunaan Media Sosial Facebook terhadap Kasus Grup Inses di Indonesia Tinjauan dari UU Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Rizka Amalia Putri Bawafie; Rizka Amelia Azis (VISA: Journal of Vision and Ideas, 2026)
The development of social media, especially Facebook, has not only facilitated communication but also had a negative impact in the form of misuse for the dissemination of pornographic content, including incest content. The emergence of online incest groups has become a serious concern because it violates moral norms, damages the social order, and has the potential to involve children as victims. This study aims to analyze the legal responsibility of perpetrators who create, manage, and disseminate incest group content on Facebook, as well as to examine law enforcement against such actions based on Law Number 11 of 2008 concerning Electronic Information and Transactions and other related regulations. The research method used is normative legal research with a regulatory approach, a case approach, and a conceptual approach, supported by criminology theory. The results of the discussion show that the act of distributing incest group content fulfills the elements of pornography and indecency as regulated in the ITE Law, the Pornography Law, and the Criminal Code. Perpetrators, including content creators and group administrators, can be prosecuted criminally and civilly. However, law enforcement still faces technical and institutional obstacles, requiring regulatory strengthening, collaboration with digital platforms, and increased digital literacy among the public.